High-pressure chemistry - James P. S. Walsh (Communications Chemistry)
Communications Chemistry is pleased to present a Collection of articles from across the broad field of high-pressure chemistry. Here, Editorial Board Member Dr James Walsh introduces the topic and takes us on a tour of the Collection content.